Teacher Education and Sustainable Change: where lies the problem? - Shahid Siddiqui (PJE, 2023)
Education is considered a powerful means of change, emancipation, and development at individual and societal levels. In Pakistan, however, it falls short of achieving these objectives despite a large number of education policies and curriculum documents since 1947 (Siddiqui, 2021). One important factor which has been downplayed in this process is the central role of teachers in the execution of any given curriculum in the classrooms. A major source of empowering teachers is teacher education. There is a growing literature on change at societal level through education in general and teacher education in particular. A change which is short lived is easy to acquire, less difficult to demonstrate but has little to contribute to sustainable development. On the other hand, long lasting change is more challenging to bring about, harder to demonstrate in short time, but is crucial for sustainable teacher development. In teacher education programmes in Pakistan a short term, visible, measurable change may be achieved but the impact of this change seldom travels to or/and stays at school. Consequently, the professional development of teachers cannot be sustained due to lack of reconceptualization of educational reforms, deficient re-entry preparation on teacher education programme, insufficient support from colleagues, want of cooperation from head teachers, dearth of follow up programmes to track the performance of teachers, and lack of follow-on programmes to update the professional (both content & pedagogical knowledge) of the trainees. This paper focuses on sustainable development from the perspective of teacher education and suggests a mechanism to sustain the educational change initiated by a teacher education programme.